Systematic Screening of Different Surface Modifiers for the Production of Physically Stable Nanosuspensions. Issue 3 (28th January 2015) - Lestari, Maria L. A. D.; Müller, Rainer H.; Möschwitzer, Jan P.
<x xml:space="preserve">Abstract</x> The role of a surface modifier is important in the formation of stable nanosuspensions. In this study, a simple and systematic screening method for selecting optimum surface modifiers was performed by utilizing a low‐energy wet ball milling method. Nine surface modifiers from different classes with different stabilization mechanisms were applied on six different models of active pharmaceutical ingredients (API). Particle size analysis showed that at concentration five times higher than the critical micelle concentration, SDS and sodium cholate (anionic surfactant) showed the highest percent success to produce stable nanosuspensions with particle size smaller than 250 nm. Similar findings were also shown by poloxamer 188 (nonionic surfactant) and hydroxypropylmethylcellulose E5 (polymeric stabilizer) at concentration 1% (w/v) and 0.8% (w/v), respectively. In addition, combinations of anionic surfactant and nonionic surfactant as well as combinations of anionic surfactant and polymeric stabilizer showed high percent success in the formation of stable nanosuspensions. In general, no correlation can be found between the physicochemical characteristics of the model API (molecular weight, melting point, log P, pKa, and crystallinity) with its feasibility to be nanosized. The concentration and the principle of stabilization of surface modifier determine the formation of stable nanosuspensions. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:1128–1140, 2015